2018
DOI: 10.7717/peerj.5309
|View full text |Cite
|
Sign up to set email alerts
|

Anxiolytic and anti-stress effects of acute administration of acetyl-L-carnitine in zebrafish

Abstract: Studies have suggested that oxidative stress may contribute to the pathogenesis of mental disorders. In this context, molecules with antioxidant activity may be promising agents in the treatment of these deleterious conditions. Acetyl-L-carnitine (ALC) is a multi-target molecule that modulates the uptake of acetyl-CoA into the mitochondria during fatty acid oxidation, acetylcholine production, protein, and membrane phospholipid synthesis, capable of promoting neurogenesis in case of neuronal death. Moreover, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 58 publications
(85 reference statements)
0
11
0
Order By: Relevance
“…However, this conclusion is derived from studies of human diseases and has not been confirmed in teleosts. A possibility needs to be explored that they may have a similar relationship in teleosts because we found that L-leucine could increase growth performance, improve metabolic activities and enhance non-specific immunities in tilapia [73] and black carp juveniles [74], and acetylcarnitine has antioxidant effects in teleosts [75].…”
Section: Discussionmentioning
confidence: 99%
“…However, this conclusion is derived from studies of human diseases and has not been confirmed in teleosts. A possibility needs to be explored that they may have a similar relationship in teleosts because we found that L-leucine could increase growth performance, improve metabolic activities and enhance non-specific immunities in tilapia [73] and black carp juveniles [74], and acetylcarnitine has antioxidant effects in teleosts [75].…”
Section: Discussionmentioning
confidence: 99%
“…Although most preclinical work on LAC in humans and rodents has focused on depression [106], existing evidence supports the interest in further exploring its potential anxiolytic effects. LAC supplementation was shown to induce anxiolytic effects in patients with minimal hepatic encephalopathy [107] and in zebrafish [108]. In the latter model, LAC was, as well, able to prevent the lipid peroxidation induced by acute stress [108].…”
Section: Drugs Targeting Mitochondrial Function and Oxidative Stress mentioning
confidence: 97%
“…LAC supplementation was shown to induce anxiolytic effects in patients with minimal hepatic encephalopathy [107] and in zebrafish [108]. In the latter model, LAC was, as well, able to prevent the lipid peroxidation induced by acute stress [108]. It should be noted, though, that other mechanisms of action -such as its reported antioxidant properties [109]-may also be implicated in LAC effects.…”
Section: Drugs Targeting Mitochondrial Function and Oxidative Stress mentioning
confidence: 99%
“…Related to its protective role in psychiatric disorders, in zebrafish, ALC prevented acute stress-induced anxiety (Pancotto, Mocelin et al 2018). In mice, ALC treatment (25-100 mg/kg, i.p.)…”
Section: L-carnitine L-mentioning
confidence: 99%